Advancing Organized Convection Representation in the Unified Model: Implementing and Enhancing Multiscale Coherent Structure Parameterization - Zhixiao Zhang; Hannah M. Christensen; Mark R. Muetzelfeldt; Tim Woollings; Robert S. Plant; Alison J. Stirling; Michael A. Whitall; Mitchell W. Moncrieff; Chih‐Chieh Chen; Zhe Feng (Journal of Advances in Modeling Earth Systems)
Abstract To address the effect of stratiform latent heating on meso‐ to large‐scale circulations, an enhanced implementation of the Multiscale Coherent Structure Parameterization (MCSP) is developed for the Met Office Unified Model. MCSP represents the top‐heavy stratiform latent heating from under‐resolved organized convection in general circulation models. We couple the MCSP with a mass‐flux convection scheme (CoMorph‐A) to improve storm lifecycle continuity. The improved MCSP trigger is specifically designed for mixed‐phase deep convective cloud, combined with a background vertical wind shear, both known to be crucial for stratiform development. We also test a cloud top temperature dependent convective‐stratiform heating partitioning, in contrast to the earlier fixed partitioning. Assessments from ensemble weather forecasts and decadal simulations demonstrate that MCSP directly reduces cloud deepening and precipitation areas by moderating mesoscale circulations. Indirectly, it amends tropical precipitation biases, notably correcting dry and wet biases over India and the Indian Ocean, respectively. Remarkably, the scheme outperforms a climate model ensemble by improving seasonal precipitation cycle predictions in these regions. The scheme also improves Madden‐Julian Oscillation (MJO) spectra, achieving better alignment with observational and reanalysis data by intensifying the simulated MJO over the Indian Ocean during phases 4 to 5. However, the scheme increases precipitation overestimation over the Western Pacific. Shifting from fixed to temperature‐dependent convective‐stratiform partitioning reduces the Pacific precipitation overestimation and further improves the seasonal cycle in India. Spatially correlated biases highlight the necessity for advances beyond deterministic approaches to align MCSP with environmental conditions.